Predicting market pig weights and fat iodine value and effect of zinc on growth performance and immune function of finishing pigs - Paulk, Chad Bennett (Kansas State University, 2014)
The optimum sampling method swine producers should use to estimate the mean and SD of pig BW within a barn was determined based upon both the time required to conduct and the precision and accuracy of each sampling method. Weighing 5 pigs from 15 pens was determined to be the optimal sampling method. This should require approximately 55 min to complete. Weighing 5 pigs from 15 pens had a CI range of 7.2 to 8.0 kg for estimating the mean BW and 5.6 kg for estimating SD. Next, a meta-analysis was conducted using data from existing literature to generate equations to predict finishing pig back, belly, and jowl fat iodine value. While numerous factors were evaluated, dietary essential fatty acids, dietary net energy content, and backfat thickness had the greatest influence on predicting iodine value of the 3 distinct fat depots. Lastly, 6 experiments were conducted to determine the effects of added Zn on growth performance, pork quality, plasma Zn, and ileal mucosal inflammation mRNA expression of finishing pigs fed diets containing ractopamine-HCl (RAC; Elanco Animal Health, Greenfield, IN). Additional Zn increased plasma Zn and reduced relative expression of IL-1β, but did not improve growth performance of pigs fed diets containing RAC in 5 of the experiments. However, in 1 of the experiments, adding Zn to diets containing RAC resulted in a trend for improved growth performance of pigs. Supplementing the RAC diets with dietary Zn decreased the percentage of type IIA fibers and tended to increase the percentage of type IIX fibers compared to pigs fed the RAC diet without added Zn. Ractopamine-HCl produced chops that were lighter and less red, but possessed reduced metmyoglobin reducing ability at the end of the display period. However, adding Zn to RAC diets increased metmyoglobin reducing ability levels at the end of the display period.
Keywords: Finishing pigs; Marketing; Iodine value; Zinc; Ractopamin-HCl; Animal Sciences (0475)